Furuncular myiasis by Cordylobia anthropophaga: a paediatric case in Italy. - Gigantesco, M.; Sabattini, C.; Gigantesco, B.; Ingordo, I.; Ingordo, V. (European Journal of Pediatric Dermatology, 2018)
Furuncular myiasis is the commonest clinical form of the disease, caused by dipterous larvae, and it is endemic in Latin America and in Africa. In western countries cases of furuncular myiasis are observed in travellers coming from tropical areas. A case of furuncular myiasis by Cordylobia anthropophaga in Livorno (Italy) is described in a 4-year-old Italian girl, who never leaved her country. This is the first case of furuncular myiasis by C. anthropophaga observed in Italy in a non-traveller patient. The Authors hypothesize that globalization and intensive migrations of people from Africa to Italy could be responsible for the infestation that in this case should be caused by the persistence of eggs in clothes of some immigrant.